Peningkatan Literasi PKK Argosari, Sedayu, Bantul melalui Membacakan Nyaring - Hariyanti, Nunik; Mahanani, Wahidah; Nabilah, Rifdah Zulfah Ghina; Salim, Mufid; Nur, Fitrinanda An (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Kalurahan Argosari, Sedayu, Bantul is strategically located because it connects three regencies, namely, Bantul, Kulon Progo, and Sleman. This strategic location needs to be balanced with sufficient knowledge and literacy for the community. This literacy ability is how an individual can process information and knowledge for life skills. Currently, the people in Argosari Village, Sedayu, Bantul are still faced with literacy and low interest in reading. Therefore, this community service program aims to improve the community's ability in the field of literacy and help reduce household waste through processing and reading aloud. The method used in training to read aloud is the stages of preparation, implementation, and after reading. The partners involved in this activity are the PKK group from Kalurahan Argosari, Sedayu, Bantul, DIY. The result of the activity is that increasing literacy can be started from the family consistently at home for 15 minutes every day by reading aloud. The impact of this activity is that the people who previously already had the provision of information became increasingly knowledgeable so that they had great potential to be applied in their respective homes.